2019
DOI: 10.1088/1361-6668/aafcd2
|View full text |Cite
|
Sign up to set email alerts
|

A simple protection evaluation method for no-insulation REBCO pancake coils during local normal-state transition

Abstract: No-insulation (NI) and metal-insulation (MI) winding techniques are promising for enhancing the thermal stability of REBCO pancake coils, toward the practical use of nuclear magnetic resonance and magnetic resonance imaging systems. The NI and MI REBCO pancake coils showed high thermal stability in many over-current tests. However, a disadvantage is a charging delay due to low turn-to-turn contact resistance. Therefore, many researchers have tried to increase turn-to-turn contact resistance to overcome the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The high contact resistance yields a short charging delay; however, too high contact resistance loses the stability. The influence of the turn-to-turn contact resistance on the thermal stability of REBCO pancake coils were discussed in [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The high contact resistance yields a short charging delay; however, too high contact resistance loses the stability. The influence of the turn-to-turn contact resistance on the thermal stability of REBCO pancake coils were discussed in [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…This could be too high for self-protection. According to the simple model from [26], the optimized turn-to-turn contact resistance should be at least one or two orders of magnitude lower than the SS co-winding value. In addition, unlike the charging decay and loss, the self-protection ability is not only dominated by the turn-to-turn contact resistance but is also closely related to the thermal conductivity of the REBCO tapes in both the circumferential and radial directions.…”
Section: Introductionmentioning
confidence: 99%
“…Although co-winding with SS tape is considered to the best strategy for solving the charging delay problem in the NI process, the SS tape is too thick (30 µm) for commercial REBCO tape (90-100 µm), and significantly decreases the engineering critical current density (Je). However, simulations [32] have shown that the turn-to-turn electrical resistivity of cowound SS tape could be too high to hinder the self-protection ability.…”
Section: Introductionmentioning
confidence: 99%